Desenvolvimento profissional docente de professoras experientes em formação contínua na ReAD - Pereira, Amarildo Gomes (2021)
This research, which focus on teacher professional development, aimed to investigate how experienced teachers understand their professional development and also in which ways they invest in continuous training; also, sought to analyze how they perceive ReAD (“Rede de Aprendizagem e Desenvolvimento da Docência” in Brazilian Portuguese, which means Teaching, Learning and Development Network) as a training space. It was carried out in the context of continuous training developed by ReAD, which actions are performed on the Moodle Platform, via the UFSCar Teachers' Portal. For the data collection process, we used the activities carried out by four experienced teachers during the modules developed in the 2nd semester of 2017 and 1st and 2nd semesters of 2018. The research is based on the qualitative approach that contributes to investigating the phenomena considering all their complexity and context; that makes it possible to understand the events from the perspective of the participating subjects. The instruments for data production and treatment were the narratives produced by the participants during the accomplishment of activities at ReAD and the narratives produced through interviews, here called as narrative interviews. The data were organized and treated by reading and coding all the material with the methodological support of Content Analysis proposed by Bardin (2009). Therefore, four groups of analysis categories were established, and from them, subcategories were created, interpreted and analyzed based on a theoretical framework presented in chapters, 1, 2 and 3. The analyzes indicate that the experienced teachers assume their professional development as a continuous process and that the intertwining between teaching and continuous training is essential for teaching and promoting the learning and development of all students. It also points out that training developed at ReAD contributed to the acquisition of new learning and knowledge and also to their personal and professional development by instigating teachers and students to discuss and reflect on the constitution of teaching and on the teaching process and its implications. The research reaffirmed the importance of online intergenerational dialogue for professionals who are at different times in the teaching career to share studies, experiences, dilemmas, difficulties and knowledge, contributing to the development of individual and collective reflections, resulting in new learning for all. It brought evidence that the working conditions impact the teacher's performance, the development of activities and the participation in discussions in the forums, which requires trainers to find strategies that suit the multiple realities and needs of the participants. In view of these results, the study indicates that the implementation of training activities considers the realities and needs of teachers, the impossibility of separating the personal and professional dimensions and the implications that work has on the personal / family life of teachers.